Variability assessment in SOC stocks influenced by different cropping systems and landuse using Geographic Information Systems (GIS) techniques in Chittoor district of Andhra Pradesh - MOHAN, M. MADHAN; PRASAD, T.N.V. K.V.; MADHURI, K.V. NAGA (Journal of Soil and Water Conservation, 2020)
The soil organic carbon (SOC) plays a pivotal role in soil biodiversity, nutrient and water recycling, agricultural productivity and sustainability of land use and cropping systems through climate change mitigation and adaptation. The main objective of current study is to assess the variability influenced by existing major land use and cropping systems of the Chittoor district during 2018. The study area located between 12°37’ to 14°08’ N latitude and 78°03’ to 79°55’ E longitude. The major land use and cropping systems identified were rice based cropping system, sugarcane based cropping system, vegetable based cropping system, groundnut based cropping system, casuarina and eucalyptus plantations, mango orchards, mulberry based cropping system, Perennial fodder crops, flower crops, forest land use, fallow and waste land use etc. Soil organic C content was highest under forest land use (10.0 g kg-1) followed by paddy-tomato (9.9 g kg-1), mango orchards >15 years (9.2 g kg-1), eucalyptus plantations (9.2 g kg-1) and sugarcane-vegetable (9.0 g kg-1). Similarly, carbon sequestration rate was highest in forest land use (28.2 Mg ha-1) followed by mango orchards >15 years age (21.1 Mg ha-1), sugarcane-vegetables (20.4 Mg ha-1) and paddy-tomato (19.9 Mg ha-1) cropping systems. The organic carbon status was very low (0.2-0.4%) in rainfed groundnut, current fallows and sugarcane-sugarcane cropping systems; medium (0.6-0.8%) in mango<5 years, sugarcane-paddy, paddy-groundnut and eucalyptus plantations; and high (>0.8%) in sugarcane-vegetables, forest land use, paddy-tomato, mango >15 yrs and perennial fodder plantations.